Mnożnik kreacji pieniądza – pojęcie, ograniczenia i krytyka - Kresak, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article presents the money creation process in the modern economy, including the role of the central bank and commercial banks in this process. The concept of money multiplier is described and set in the context of Fed’s monetary policy since 1970s. Special attention is paid to the decrease of the M1 multiplier below the value of one, which accompanied the quantitative easing after the crisis arousal in 2008. Then, the main constraints are mentioned of commercial banks in the process of money creation (impeding the full utilization of the multiplier potential): bank profitability and competitiveness, risk of bank runs, demand for currency, limitations concerning credit collaterals and those resulting from monetary policy, prudential regulations, and the behaviors of bank clients. The paper also reports on arguments critical toward the multiplier approach and suggests to perceive the money supply in the modern economy as an endogenously determined phenomenon: first, commercial banks grant as many credits (thus creating money) as they can owing to the market situation; then, they turn to the central bank to provide reserves. The latter provides reserves (monetary base) as the lender of last resort, aiming to control the interest rate, and not money quantity itself. The conclusions are significant for monetary policy and economic education, as the endogenous approach to money supply can explain why the quantitative easing, contrary to some concerns, did not automatically translate into a considerable increase of credit expansion and price inflation.
Keywords: pieniądz; mnożnik kreacji pieniądza; polityka monetarna